Answer:
The basis is <1/√3, -2/5 x + 1 /15, 0.4825x^2 - 0.6466 x -0.3748>
Explanation:
First, we calculate the norm of f
||f||² = <f,f> = f(-1)²+f(0)²+f(1)² ) = 3*(-7)² = 147
Therefore, ||f|| = √147
We take as the first element of the basis
![(-7)/(√(147)) = (1)/(√(3)) .](https://img.qammunity.org/2020/formulas/mathematics/high-school/dgkqirm10kcket255mqhsdymt914m9az2c.png)
we define
![\tilde{g}(x) = g(x) - <g,v1> * v1](https://img.qammunity.org/2020/formulas/mathematics/high-school/oxld66qpuplvo11u2padr65o90bdkg1mk1.png)
lets calculate <g,v1>
g(-1) = 9
g(0) = 5
g(1) = 1
v1(-1) = v1(0) = v1(1) = 1/√3
Then <g,v1> = 9*7/√(147)+5*7/√(147)+1*7/√(147) = 15*7/√(147) = 105/√147
and <g,v1>v1 = 105/√(147) * 7/√(147) = 735/147 = 35/9
Therefore,
![\tilde{g}(x) = -4x+5-35/9 = -4x + 2/3](https://img.qammunity.org/2020/formulas/mathematics/high-school/ipyuzbunkul5rvpc1twuwpykgbx9eyfm8v.png)
Now, lets calculate the norm, for that
![\tilde{g}(-1) = 14/3](https://img.qammunity.org/2020/formulas/mathematics/high-school/s0pbok65dk5qm1y26o0byymdm6258v9zwv.png)
![\tilde{g}(0) = 2/3](https://img.qammunity.org/2020/formulas/mathematics/high-school/x9xo8ehcmictqaozm53eg7xqn6kgoywc39.png)
![\tilde{g}(1) = -10/3](https://img.qammunity.org/2020/formulas/mathematics/high-school/c8otf4oj4ggr4dscguqu1ct3vh0pxnq6yd.png)
As a result,
![< \tilde{g}, \tilde{g} > = (14/3)^2+(2/3)^2+(-10/3)^2 = 100, hence [tex] || \tilde{g} || = 10](https://img.qammunity.org/2020/formulas/mathematics/high-school/lulcf8v3vhjovvga9s12u67n0wkzzgve3f.png)
We take
![v2 = \tilde{g} / 10 = -2/5 x + 1 /15](https://img.qammunity.org/2020/formulas/mathematics/high-school/daz4adbdiza0krvu3q1r06i9tw69ik0u4x.png)
Finally, we take
![\tilde{h}(x) = h(x) - v1 <h,v1> - v2 <h,v2>](https://img.qammunity.org/2020/formulas/mathematics/high-school/6vsjn03psni9la72afjpg774x9f7gq11od.png)
Note that
h(-1) = 7
h(0) = -5
h(1) = -9
v1(-1) = v1(0) = v1(1) = 7/√(147) = 1/√3
v2(-1) = 7/15
v2(0) = 1/15
v3(1) = -1/3
Thus,
<h,v1>v1 = (7-5-9)*(7/√(147))² = -7/3
<h,v2>v2 = ((7*7/15) + (-5*1/15) + (-9*-1/3)) * (-2/5 x + 1 /15) = -66/25 x + 11/25
As a consecuence, we have that
![\tilde{h}(x) = 4x^2-8x-5 +7/3 + 66/25x -11/25 = 4x^2-5.36x-233/75](https://img.qammunity.org/2020/formulas/mathematics/high-school/cbdwmghv9shqeckt0j46knauehz9e42ltx.png)
since
![\tilde{h} (-1) = 469/75; \tilde{h} (0) = 233/75: tilde{h}(1) = -67/15](https://img.qammunity.org/2020/formulas/mathematics/high-school/hu46rdvgo6mtjp9e1hdtk3gs0rehlnm5nm.png)
we obtain that
![||\tilde{h}|| = \sqrt{<\tilde{h},\tilde{h}>} = √(86.706) = 8.288](https://img.qammunity.org/2020/formulas/mathematics/high-school/tyd0sac1ten23jdce7gkqgs768jty72moc.png)
Therefore,
![v3 = \tilde{h}/8.288 = (4x^2-5.36x-233/75)/8.288 = 0.4825x^2 - 0.6466 x -0.3748](https://img.qammunity.org/2020/formulas/mathematics/high-school/e0ger4urbw2pxt1jwons6qs5vhpug4uz0q.png)
The basis is <1/√3, -2/5 x + 1 /15, 0.4825x^2 - 0.6466 x -0.3748>